Folate‐Conjugated Polylactic Acid–Silica Hybrid Nanoparticles as Degradable Carriers for Targeted Drug Delivery, On‐Demand Release and Simultaneous Self‐Clearance. Issue 7 (2nd June 2016) - Ma, Zhifang; Li, Xiaolei; Jia, Xiaodan; Bai, Jing; Jiang, Xiue
Abstract: Improving the therapeutic efficacy of cancer chemotherapy and reducing the side effects in patients are appealing goals but represent critical challenges. In this work, a novel SiO2 ‐based nanocarrier coated with polylactic acid and folate has been fabricated to destroy tumors in vivo. Folic acid promotes the targeted intracellular delivery of drug molecules to cancer cells overexpressing the folate receptor for improving the efficacy of the therapy. The polylactic acid layer prevents the premature leakage of drug until the polylactic acid is degraded as a response to low pH and enzymes; this mechanism is designed for sustained and on‐demand drug release to prevent undesired side effects. Escape of the drug molecules then triggers decomposition of the SiO2 carrier, improving its elimination from the patient. The strategy of combining the engineering flexibility of inorganic nanocarriers with the stimuli‐responsive biodegradability of organic molecules will offer new directions in on‐demand and sustained drug release for chemotherapy. Abstract : Wait before removing your coat : A novel SiO2 ‐based nanocarrier coated with polylactic acid and folate (FA) has been used to destroy tumors (see figure). This nanocomposite can target the delivery of doxorubicin (Dox) without premature leakage of the drug before the polylactic acid is degraded. Decomposition of the SiO2 carrier improves its clearance from biological tissues.